Gene-repaired iPS cells as novel approach for patient with osteogenesis imperfecta - Fus-Kujawa, Agnieszka; Mendrek, Barbara; Bajdak-Rusinek, Karolina; Diak, Natalia; Strzelec, Karolina; Gutmajster, Ewa; Janelt, Kamil; Kowalczuk, Agnieszka; Trybus, Anna; Rozwadowska, Patrycja; Wojakowski, Wojciech; Gawron, Katarzyna; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The benefits of patient’s specific cell/gene therapy have been reported in relation to numerous genetic related disorders including osteogenesis imperfecta (OI). In OI particularly also a drug therapy based on the administration of bisphosphonates partially helped to ease the symptoms. However, the continuous development of new methods and tools including novel polymer Poly[N,N-Dimethylaminoethyl Methacrylate-co-Hydroxyl-Bearing Oligo(Ethylene Glycol) Methacrylate] Arms (P(DMAEMA-co-OEGMA-OH) with star-like structure has never been reported before in treatment of OI patients. In this controlled trial, fibroblasts derived from patient diagnosed with OI type II have been successfully reprogrammed into induced Pluripotent Stem cells (iPSCs) using Yamanaka factors. Those cells were subjected to repair mutations found in the COL1A1 gene using homologous recombination (HR) approach facilitated with star polymer (STAR) as a carrier of the genetic material. Delivery of the correct linear DNA fragment to the OI patient's cells resulted in the repair of the DNA mutation with an 84% success rate. IPSCs showed 87% viability after STAR treatment and 82% with its polyplex. (Funded by National Science Centre, Contract No. UMO-2020/37/N/NZ2/01125).